2005
DOI: 10.1158/0008-5472.can-04-3488
|View full text |Cite
|
Sign up to set email alerts
|

DNA Adducts and Lung Cancer Risk: A Prospective Study

Abstract: Objectives were to investigate prospectively the ability of DNA adducts to predict cancer and to study the determinants of adducts, especially air pollutants. DNA adducts were measured in a case-control study nested in the European Prospective Investigation into Cancer and Nutrition (EPIC) investigation. Cases included newly diagnosed lung cancer (n = 115), upper respiratory cancers (pharynx and larynx; n = 82), bladder cancer (n = 124), leukemia (n = 166), and chronic obstructive pulmonary disease or emphysem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
1
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 39 publications
6
91
1
8
Order By: Relevance
“…12 Therefore, it is not necessarily relevant, at least in causal assessment, to distinguish among single pollutants; rather, they might interact in unpredictable ways. O 3 has been found to damage DNA in 2 epidemiological studies, including the present one, 13,14 but its role is more difficult to assess because of strong negative association with other 2 , 27 vs <27 lg/m 3 for PM10, and 11 vs <11 lg/m 3 for SO 2 (see text).-2 As in footnote 1 but additionally adjusted by BMI, education, intake of fruit and vegetables, intake of meat, intake of alcohol, physical activity.-3 As in footnote 1 but additionally adjusted by cotinine.- 4 As in footnote 1 but additionally adjusted by occupational index (see text).…”
Section: Discussionsupporting
confidence: 49%
“…12 Therefore, it is not necessarily relevant, at least in causal assessment, to distinguish among single pollutants; rather, they might interact in unpredictable ways. O 3 has been found to damage DNA in 2 epidemiological studies, including the present one, 13,14 but its role is more difficult to assess because of strong negative association with other 2 , 27 vs <27 lg/m 3 for PM10, and 11 vs <11 lg/m 3 for SO 2 (see text).-2 As in footnote 1 but additionally adjusted by BMI, education, intake of fruit and vegetables, intake of meat, intake of alcohol, physical activity.-3 As in footnote 1 but additionally adjusted by cotinine.- 4 As in footnote 1 but additionally adjusted by occupational index (see text).…”
Section: Discussionsupporting
confidence: 49%
“…Recent publications have reported associations with biomarkers of environmental exposures in the GENAIR cohorts, including bulky DNA adducts in WBC (12), and biomarkers of genetic susceptibility, such as polymorphisms in genes involved in carcinogen metabolism, detoxification, and DNA repair (17). 32 Here, we have reanalyzed these previously reported data with respect to the presence of mutations in plasma DNA (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…GENAIR is a case-control study nested within the EPIC cohort, aiming at studying the relationship between some types of cancers and air pollution or environmental tobacco smoke (12). Cases are subjects with bladder, lung, or UADT cancers or leukemia, all newly diagnosed after recruitment.…”
Section: Methodsmentioning
confidence: 99%
“…Neither age nor race was associated with BCR in our study population, but elevated DNA adduct levels had the strongest association with BCR in younger African-American cases. The combination of high adduct levels and younger age has been associated with higher risk of lung (53) and colorectal (54) cancer. Hu et al (50) found lower nucleotide excision repair capacity was a stronger risk for prostate cancer in men younger than 60 years old and that the nucleotide excision repair capacity level was lower in younger cases, suggesting that deficient nucleotide excision repair capacity could contribute to early onset of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%